Cross sectional associations of physical activity and sleep with mental health among Chinese university students - Bo Li; Shan-shan Han; Yu-peng Ye; Ya-xing Li; Shu-qiao Meng; Shuo Feng; Han Li; Zhong-lei Cui; Yang-Sheng Zhang; Yao Zhang; Qing Zhang; Guang-xu Wang; et al. (Scientific Reports)
Abstract Objective This study aimed to examine the levels of physical activity (PA), sleep, and mental health (MH), specifically depression, anxiety, and stress, among Chinese university students. It also aimed to analyze the influencing factors of MH, providing a theoretical foundation for developing intervention programs to improve college students’ mental health. Methods A stratified, clustered, and phased sampling method was employed. In September 2022, a survey was conducted among 36,756 university students from 104 higher education institutions across 31 provinces, autonomous regions, and municipalities in China. The participants’ PA behaviors, sleep patterns, depressive symptoms (use the CES-D), anxiety symptoms (use the GAD-7), smoking and drinking behaviors, and demographic information were assessed through an online questionnaire using Questionnaire Star software. Results A total of 30,475 valid questionnaires were completed. The proportion of university students engaging in light-intensity PA was 77.6%. The prevalence of insufficient sleep was 39.5%, whereas the prevalence of poor sleep quality was 16.7%. The prevalence of depressive symptoms was 10%, and the prevalence of anxiety symptoms was 23.3%. Binary logistic regression analysis revealed that engaging in moderate to high-intensity PA and having sufficient and high-quality sleep were associated with a lower likelihood of depressive symptoms (OR = 0.207–0.800, P < 0.01), whereas appropriate sleep duration and higher sleep quality were associated with a lower likelihood of anxiety symptoms (OR = 0.134–0.827, P < 0.001). Conclusion The intensity of PA among university students is predominantly light, and the reported rate of insufficient sleep is relatively high. Moderate to high-intensity PA and sufficient high-quality sleep may alleviate MH issues among college students, with an interaction effect observed among PA, sleep, and depression symptoms. Future studies should further explore targeted interventions combining PA and sleep behaviors to enhance the MH of university students.